Pelatihan Aplikasi Pupuk Organik Cair (POC) Pada Tanaman di Kampung Cilokotot, Kabupaten Bandung - Muliati, Lia; Sitawati, Rini; Murdikaningrum, Galu (Universitas Insan Cendekia Mandiri, 2026)
The continued use of inorganic fertilizers has a negative impact on the environment, necessitating a more sustainable alternative, liquid organic fertilizer (POC). Cilokotot Village, South Margahayu Village, is a tempeh production center that produces liquid waste and cow dung that have the potential to be processed into biogas and POC. This Community Service (PkM) activity aims to provide education and training to the community on techniques for applying POC, a byproduct of biogas fermentation, to plants. The methods used included equipment preparation, formula determination experiments, and training through lectures and hands-on practice. The results showed that the POC from anaerobic leachate has an acidic pH (3–5), requiring a neutralization process to reach the ideal pH (5.5–7) through dilution techniques, the addition of alkaline materials (lime or rice husk ash), or re-fermentation. The training participants, consisting of tempeh artisans, demonstrated high enthusiasm and successfully improved their understanding and technical skills in fertilizing plants with a dilution dosage of 1:10 to 1:30. The conclusion of this activity is that the community is now able to independently manage waste into useful products, which is expected to reduce dependence on chemical fertilizers and increase local economic potential.